Factors affecting the willingness of farmers to sell directly to direct market channels the case of smallhoder vegetable farmers in Marilog, Davao City, Philippines - Garcia, Ma. Karysa F.
Marketing of agricultural products is one key area in the Philippine agriculture that could help farmers achieve higher income and improve economic well-being. An alternative for the vegetable farmers to attain higher margin is to sell directly to direct market channels (DMCs). This study primarily aims to assess the willingness of farmers to sell directly to DMCs namely concessionaire, purveyor, institutional buyer and supermarket C. Purposive sampling was used to select the respondents, and one-on-one survey interview was conducted in Marilog. Probit regression was utilized to determine the factors that significantly affect the farmers? willingness to sell directly to DMCs. Results showed that age, years of farming experience, membership to cluster, volume of beans, volumes of ?other? vegetables consisting mainly of bitter gourd and yard long bean, and the selling prices of pechay and eggplant are significant at 95% confidence interval. These factors positively influences the dependent variable. In contrast, the types of vegetables grown in the farm and the volume and selling price of squash negatively affects the dependent variable and significant at 90% confidence interval. Through qualitative analysis, the study found out that the buyers? price offer, farmers? loyalty to suki buyer, quality requirements, financing arrangements, consistency of market to buy from farmers, condition of road from farm to market, selling arrangement, and lack of experience in marketing also affect the farmers? willingness to sell directly to DMCs. Thus, the study recommends that the Local Government Unit (LGU) create and facilitate a drop-off point in Marilog where farmers and buyers could easily trade. The stakeholders should also provide more market information and conduct trainings to farmers. In addition, it is recommended for the DMCs to consider pick-up arrangement and lesser business requirements. Lastly farmers are advised to attend more training and join clusters of farmers? associations.